Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons